Dual-targeting peptides@PMO, a mimetic to the pro-apoptotic protein Smac/DIABLO for selective activation of apoptosis in cancer cells - Eros Di Giorgio; Annalisa Ferino; Weizhe Huang; Sigrid Simonetti; Luigi Xodo; Rossella De Marco (Frontiers Media S.A., 2023)
The refractoriness of tumor cells to apoptosis represents the main mechanism of resistance to chemotherapy. Smac/DIABLO mimetics proved to be effective in overcoming cancer-acquired resistance to apoptosis as a consequence of overexpression of the anti-apoptotic proteins XIAP, cIAP1, and cIAP2. In this work, we describe a dual-targeting peptide capable of selectively activating apoptosis in cancer cells. The complex consists of a fluorescent periodic mesoporous organosilica nanoparticle that carries the short sequences of Smac/DIABLO bound to the αvβ3-integrin ligand. The dual-targeting peptide @PMO shows significantly higher toxicity in αvβ3-positive HeLa cells with respect to αvβ3-negative Ht29 cells. @PMO exhibited synergistic effects in combination with oxaliplatin in a panel of αvβ3-positive cancer cells, while its toxicity is overcome by XIAP overexpression or integrin β3 silencing. The successful uptake of the molecule by αvβ3-positive cells makes @PMO promising for the re-sensitization to apoptosis of many cancer types.